The state of antibiotic stewardship programs in 2021: The perspective of an experienced steward - Tamar F. Barlam (Cambridge University Press, 2021)
Recognition of antibiotic stewardship programs (ASPs) as essential components of quality health care has dramatically increased in the past decade. The value of ASPs has been further reinforced during the coronavirus disease 2019 (COVID-19) pandemic because these programs were instrumental in monitoring antibiotic use, assessing emerging COVID-19 therapies, and coordinating implementation of monoclonal antibody infusions and vaccinations. ASPs are now required across hospital settings as a condition of participation for the Centers for Medicare and Medicaid Services and for accreditation by The Joint Commission. In the 2019 National Healthcare Safety Network annual survey, almost 89% of hospitals met the Seven Core Elements for ASPs defined by the Centers for Disease Control and Prevention. More than 61% of programs were co-led by physicians and pharmacists, evidence of the leadership role of both groups. ASPs employ many strategies to improve prescribing. Core interventions of preauthorization for targeted antibiotics, prospective audit and feedback, and development of local treatment guidelines have been supplemented with numerous emerging strategies. Diagnostic stewardship, optimizing duration of therapy, promoting appropriate conversion from intravenous to oral therapy, monitoring at transitions of care and hospital discharge, implementing stewardship initiatives in the outpatient setting, and increasing use of telemedicine are approaches being adopted across hospital settings. As a core function for medical facilities, ASP leaders must ensure that antibiotic use and ASP interventions promote optimal and equitable care. The urgency of success becomes progressively greater as complex patterns of antibiotic resistance continue to emerge, exacerbated by unpredictable factors such as a worldwide pandemic.